Nicole Bergk Pinto, Étude et édition critique du Tournoiement Antecrist : dit allégorique attribué à Huon de Mery - Nicole Bergk Pinto (Perspectives Médiévales)
The Tournoiement Antecrist is an allegorical poem, composed around 1235 by a cleric named Huon. Though narrating the age-old battle between Good and Evil, the author succeeded in creating an original work that integrates both lay culture and humour. The poem is conserved in a fairly large number of manuscripts (10 manuscripts and 2 fragments), which attest to its success, and is considered to have played a seminal role in founding the French allegorical tradition. Despite its cultural importance, the Tournoiement had been little studied. To date, there existed no reliable critical edition of the work. This no doubt explains in part why literary studies remained few in number and are often cursory. My research intends to remedy this situation by producing a new edition and a study that shed new light on the work and its place in literary history. Based on an in-depth examination of all extant witnesses, the edition offers a critical text, accompanied by a complete apparatus and a detailed study of the manuscript tradition, as well as linguistic analyses, critical notes, a glossary and an index. The literary study examines the poem’s composition and style, the complex intertextual relationships linking it to other works, and the evidence for its medieval reception, in order to arrive at a better understanding of a work whose intellectual and aesthetic significance was largely recognized, but remained to be fully assessed.